SATIRE IS A LITERARY TOOL OF V.SHUKSHIN (On the example of the novel “Lyubavins”) (Scientific journal of the Fergana State University, 2025)
The article examines the satirical representation of reality by V.Shukshin in the novel "Lyubavins". The formation of people's life and socio-historical experience plays a huge role for the writer, he introduces material that will teach the ability to squeeze words like a fist and unfold those that have already been squeezed by others, proverbs and aphorisms contributed to the development of thinking. Reality with a satirical interpretation is repeatedly highlighted, while emphasizing neutrality, which can be explained by the author's inconsistency.Strange textual facts that have no explanation are a vivid example of V. Shukshin's confusion in understanding temporal connections. In his literary work, the author uses hyperbole to emphasize the absurdity of the situation. The main signs of this exaggerated emphasis are loss of vital energy and unpredictability. The work, rich in exaggerations, arouses great interest and brings pleasure to readers. Exaggeration is used to emphasize certain emotions or dramatic moments, emotions, or to add a comic effect. It gives the author the opportunity to play with the reader's imagination. The satirical exploration of reality gives the work a special status, turns any phrase, folk stories into a joke, which gives a special charm to fresh humorous statements.